Functioning of nominative sentences in Lyna Kostenko poetry (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2013)
The author describes types and functional role of nominative sentences used in Lyna Kostenko poetry in particular in the collection «Мадонна Перехресть».
Keywords: nominative sentence; figurativeness; emotionality; expressivity